Hubungan Kecukupan Kalori dan Protein dengan Status Malnutrisi pada Pasien Hemodialisis di Klinik Ginjal Lestari Semarang - Khairunnisa, Khalifia; Widiasih, Esti; Rohmani, Afiana; Riani, Risky Ika (Buletin Farmatera, 2025)
Abstract: Hemodialysis patients have several side effects from treatment, including possible malnutrition due to their decreased nutritional status.  Malnutrition in hemodialysis patients can occur due to increased protein catabolism, loss of nutrients during the dialysis process, and impaired food intake due to anorexia, nausea, and vomiting. The purpose of this study was to determine the relationship between calorie and protein adequacy and malnutrition status in hemodialysis patients at the Lestari Kidney Clinic Semarang. This study uses a quantitative design of observational analytics with a cross-sectional approach. The research sample of 47 hemodialysis patients at the Lestari Kidney Clinic Semarang in 2025 was selected using a purposive sampling method that met the inclusion and exclusion criteria. Calorie and protein adequacy measurements were carried out using the 3x24-hour food recall method, while malnutrition status was assessed using the Dialysis Malnutrition Score (DMS). Data analysis was carried out with the Spearman Rank test to see the relationship between calorie and protein adequacy and malnutrition status. The analysis showed a significant relationship between calorie adequacy and malnutrition status (p = 0.034, r = -0.310) and protein adequacy with malnutrition status (p = 0.020, r = -0.338). The association showed a negative correlation with weak correlation strength, meaning the higher the calorie and protein adequacy, the lower the patient's malnutrition score. There was a relationship between calorie and protein adequacy and malnutrition status in hemodialysis patients at the Lestari Kidney Clinic.